Strategi DP3AP2KB dalam Memberikan Perlindungan dan Pencegahan Korban Sodomi Siswa Sekolah Dasar di Kota Padang - Anggun, Anggun; Frinaldi, Aldri (JESS (Journal of Education on Social Science); Vol 3 No 2 (2019): Special EditionDO - 10.24036/jess/vol3-iss2/189, 2019)
As many as 56.46% of cases of violations of children's rights are sexual crimes and the rest is physical violence and child abuse. This research uses descriptive qualitative research case. Informants in this study were determined by purposive sampling, several research informants namely the Head of the Protection of Women's Rights and Child Protection in the Office of the Women's Empowerment Office for Child Protection, Population and Family Planning Control and the Office of Education for violence against children in the context of sexual violence every year is always increasing. The results of this study indicate that the strategies and efforts of the Women's Empowerment Office for Child Protection, Population Control and Family Planning (DP3AP2KB) in providing protection and prevention of sodomy victims to elementary school students in the city of Padang can be said to be quite good and but not yet comprehensive in minimizing cases. The strategies used by the P3AP2KB Office have generally been planned and ordered according to stages. However, the strategy used was not optimal due to the inaccurate targeting of the strategy used by the Padang City P3AP2KB Office .